The Effect of Corporate Sustainability Performance on the Values of Companies Listed in the Sri Kehati Index - Dahlia Pinem; Sindi Aulia (Formosa Journal of Sustainable Research, 2022)
This study aims to determine and analyze the effect of Corporate Sustainability Performance as measured by the community component, employee component, environmental component and corporate governance component on corporate value as proxied by the Tobins Q ratio. The approach used in this study is a quantitative approach. This research was conducted on companies that are constituently listed on the Sri Kehati Index by taking a sample of 22 companies using a total sampling technique. Panel data regression analysis was used in this study using Eviews 12. The results of this study indicate that (1) the components of society, employees, environment and corporate governance have an effect on firm value, (2) community components have an effect on firm value, (3) employee component has no effect on firm value, (4) environmental component has no effect on firm value and (5) corporate governance component has no effect on firm value